Réponses

Meilleure réponse !
2014-04-14T18:43:32+02:00
36)
Résoudre les équations suivantes :
a) 2 (x - 5) = 3 (-x + 5)
2x - 10 = -3x + 15
2x + 3x = 10 + 15
5x = 25
x = 25/5
x = 5

b) - 3 (a + 3) = 5 (3 - a) + 2
-3a - 9 = 15 - 5a + 2
- 3a + 5a = -9 + 15 + 2
2a = 8
a = 8/2
a = 4

c) m - (5 - 2m) = 3m + 4
-5m + 3m = 3m + 4
-5m + 3m - 3m = 4
-5m =  4
m = - 5/4
m = - 1,25

d) 2 (p - 3) + 5 (p - 7) = 0
2p - 6 + 5p - 35 = 0
2p + 5p = 6 + 35
7p = 41
p = 41/7
p ≈ 5,85

37)
Résoudre les équations suivantes :
a) 6 + 2 (x - 5) = 2 (-x + 4)
6 + 2x - 10 = -2x + 8
2x + 2x = -6 + 10 + 8
4x = 12
x = 12/4
x = 3

b) 13 - 3 (-a + 3) = 5 (3 - a) + 2
13 + 3a - 9 = 15 - 5a + 2
3a + 5a = -13 + 9 + 15 + 2
8a = 13
a = 13/8
a ≈ 1,625

c) 2m - 3 (5 - 3m) = 3m + 4
2m - 15 + 9m = 3m + 4
2m + 9m - 3m = 15 + 4
8m = 19
m = 19/8
m ≈ 2,375

d) 2 (n - 3) - 5 (n - 7) = 0
2n - 6 - 5n + 35 = 0
2n - 5n = 6 - 35
-3n = -29
n = 29/3
n ≈ 9,666